2020
DOI: 10.1111/ijcp.13767
|View full text |Cite
|
Sign up to set email alerts
|

QTc prolongation among hydroxychloroquine sulphate‐treated COVID‐19 patients: An observational study

Abstract: Background The liberal administration of hydroxychloroquine‐sulphate (HCQ) to COVID‐19 patients has raised concern regarding the risk of QTc prolongation and cardiac arrhythmias, particularly when prescribed with azithromycin. We evaluated the incidence of QTc prolongation among moderately and severely ill COVID‐19 patients treated with HCQ and of the existence of concomitant alternative causes. Methods All COVID‐19 patients treated with HCQ (between Mar 1 and Apr 14, 2020) in a tertiary medical centre were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Hydroxychloroquine was widely prescribed during the first wave. However, its use has not been shown to improve COVID-19 outcomes and indeed, it may even increase mortality due to cardiac arrhythmia, especially in old and very old vulnerable patients who have significant comorbidities [ 37 ]. Given that the use of hydroxychloroquine in our series was less frequent in NC than in CAC patients, the overall higher IHM observed in NC patients seems to be independent of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine was widely prescribed during the first wave. However, its use has not been shown to improve COVID-19 outcomes and indeed, it may even increase mortality due to cardiac arrhythmia, especially in old and very old vulnerable patients who have significant comorbidities [ 37 ]. Given that the use of hydroxychloroquine in our series was less frequent in NC than in CAC patients, the overall higher IHM observed in NC patients seems to be independent of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study in SARS-CoV-2 patients reported an increase of 13 (IQR 9 -16) ms. 41 Other studies reported QTcF-prolongation after hydroxychloroquine treatment only in a minority of their cases. 44,45 E.g., an average increase of the QTcF-interval of 1.8% was observed in a cohort of 219 hospitalized and ambulatory SARS-CoV-2 patients who were treated with a total dose of 2800 mg hydroxychloroquine, although combined with other antiviral drugs. 40 In another cohort of 111 hospitalized SARS-…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the studies included in the two groups is provided in Data S1 12–194 . The literature search yielded a total of 826 citations.…”
Section: Data Extractionmentioning
confidence: 99%